2017
DOI: 10.22146/jsp.28679
|View full text |Cite
|
Sign up to set email alerts
|

Public Trust and Regulatory Compliance

Abstract: Several studies have proven that public trust in government improves the level of policy or regulation acceptance and reduce administrative costs. In contexts where trust in government is high, citizens tend to be more willing to voluntarily comply with public policies. This article aims to explore issues of trust and distrust toward government, seen from the aspect of public compliance, both to rules or policies. The level of public trust toward government is expressed by giving its support through its conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
6
Order By: Relevance
“…For example, Harring and Jagers (2013) found that political trust significantly affects people's attitudes towards an increased tax on carbon dioxide. Likewise, and inversely, Widaningrum (2017) showed that non-compliant behaviors in Indonesia regarding the law on traffic and road transport, and the local regulation on street vendor management expresses stemmed from and highlighted a form of low-trust in government. As such, they measured the trust-effect on a case-specific level.…”
Section: Public Policy Guidelines and Trust During The Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Harring and Jagers (2013) found that political trust significantly affects people's attitudes towards an increased tax on carbon dioxide. Likewise, and inversely, Widaningrum (2017) showed that non-compliant behaviors in Indonesia regarding the law on traffic and road transport, and the local regulation on street vendor management expresses stemmed from and highlighted a form of low-trust in government. As such, they measured the trust-effect on a case-specific level.…”
Section: Public Policy Guidelines and Trust During The Pandemicmentioning
confidence: 99%
“…Here, burgeoning COVID-19 literature is rife with indications of how trust plausibly influences compliance (e.g., Toshkov et al, 2020;Devine et al, 2021). This is in addition to pre-pandemic literature offering similar indications (e.g., Widaningrum, 2017). Second, there are robust measurement schemes for trust and excess mortality, chief of which is the Eurobarometer trust data and official equivalized excess mortality information (European Commission, 2021a, 2021b.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, greater trust can give rise to many alternatives and motivations for people to follow the institution's decisions well and obediently (Silalahi, 2011). In line with that, in Indonesia, public trust in institutions increases public acceptance of established policies and regulations, making people more prepared and open to complying with public policies (Widaningrum, 2017). Public trust is an important thing always to be maintained by the government owing to inappropriate policies and the government's inability to meet community expectations.…”
Section: Trust Towards Religious Court In Resolving Sharia Economic D...mentioning
confidence: 88%
“…Moreover, the literature showed that willingness to use a contact-tracing application is associated with trust in the government. In general, high public trust in the government will facilitate the government in implementing policies and rules [48,49]. Regarding contact tracing adoption, people who trust the government to handle the health crisis seem more willing to accept and use contact-tracing applications [2].…”
Section: Hypotheses 5 (H5) People's Attitudes Towards the Immuni Application Influence The Download And Use Of Itmentioning
confidence: 99%